The Influence of Digital Marketing and Product Quality on Customer Satisfaction and Its Implications on Customer Loyalty at Master Jaya Store in Depok, West Java, Indonesia - Kasmad (Sinergi International Journal of Management and Business, 2023)
Digital marketing currently plays a vital role in introducing a product and directly engaging customers. Digital marketing techniques have considerable potential to enhance customer preferences for purchasing a product, especially among young individuals who tend to readily adapt to digital products. The research is conducted to understand the influence of digital marketing and product quality on customer loyalty with customer satisfaction as a mediator among students at the School of Economics in Bogor. The study employed primary data through questionnaires distributed to 50 respondents. Path analysis results revealed that digital marketing has a direct, positive, and significant impact on customer loyalty, whereas product quality does not directly affect loyalty. Indirectly, digital marketing and product quality significantly influence loyalty through customer satisfaction.